Pollution assessment and spatial distribution of roadside agricultural soils: a case study from India. - Dogra, Naman; Sharma, Manik; Sharma, Anket; Keshavarzi, Ali; Minakshi; Bhardwaj, Renu; Thukral, Ashwani Kumar; Kumar, Vinod (International Journal of Environmental Health Research, 2020)
The present work studied the pH, organic carbon, phosphorus (P), calcium (Ca), magnesium (Mg), and heavy metals Cu, Cr, Co and Pb in roadside agricultural soils of Jalandhar environs of Punjab, India. A total of 120 samples in triplicates were collected from different sites for assessment of heavy metal pollution. The mean values of Cu, Cr, Co and Pb were found below the permissible limits of Indian and Swedish soil limits. Principal component analysis (PCA) showed that heavy metals have different sources of origin. The results of contamination factor (CF), geoaccumulation index (Igeo), degree of contamination (Cd) and potential ecological risk index (RI) showed low contamination and ecological risks of heavy metals in roadside agricultural soils, respectively. The maps of spatial analysis indicated that northern region of the study area is more polluted.